Investigating Factors Influencing The Incidence of Anemia Among Adolescent Girls at Senior High School In Samarinda City - Rahma, Rosyida Muthia; Zuhratunnisa, Aqilah; Nazhirotin, Talitha Syadza; Pawestri, Aulia; Hutapea, Reza Jonathan; Nugroho, Setyo; Duma, Krispinus (Mulawarman International Conference on Tropical Public Health, 2025)
Anemia is a condition of not having enough number of red blood cells or hemoglobin to carry oxygen to supply the body's physiological needs. The occurrence of anemia in adolescent girls can be influenced by various factors. This study aimed to determine the factors that influence the incidence of anemia in adolescent girls at Senior High School in Samarinda city. The design of this research was analytical observational with the cross sectional approach. Primary data was obtained using the interview with Knowledge, Attitudes, and Practice (KAP) Questionnaire and SAMANTA Questionnaire, and hemoglobin levels were examined using haemometer digital. The sampling technique used was purposive sampling with 98 respondents represented by a 10th grade student in Senior High School 6 Palaran District. The bivariate analysis used was the chi-square test. The results of the analysis between anemia status and the level of knowledge about anemia, nutritional status, menstrual patterns, parental income, and maternal education sequentially obtained showed p-values of 0.645; 0.279; 0.654; 0.551; 0.776. Based on the results of the study, it is concluded that there is no significant relationship between the factors and the incidence of anemia in adolescent girls at Senior High School 6 Palaran District.